Antioxidant Effect of Lycium barbarum Leaf through Inflammatory and Endoplasmic Reticulum Stress Mechanism - Lee, So Rok (Antioxidants (Basel), 2020)
Although the prevalence and incidence of inflammatory bowel disease (IBD), a defective immune response of the gastrointestinal tract, has been increasing in North America and Western Europe, recent studies have shown that this disease is also increasing rapidly in Asia. Several studies have been searching for functional foods that can prevent or reduce IBD symptoms because the drug treatments for IBD are expensive with complications. Genome-Wide Association Study (GWAS), an observational study of a genome-wide set of genetic variants in different individuals, showed that endoplasmic reticulum (ER) stress is one of the causes of IBD. Previously, we reported the effects of Lycium barbarum fruit and this study investigated the effects of Lycium barbarum leaf (LL) on inflammation and ER stress of the intestine. The paracellular permeability, antioxidant, and anti-inflammatory response were measured on polarized Caco-2 cells. The ER stress pathway and pro-inflammatory cytokines were evaluated on MEF-knockout cell lines, and on the intestines of the mice fed a high-fat diet with lipopolysaccharide-induced inflammation. Our data showed that the LL pretreatment strengthened the tight junction integrity and reduced NO production both in the presence and in the absence of inflammation. Furthermore, LL inhibited ER stress and inflammation via IRE1α and XBP1 in vitro as well as in the inflamed intestines of mice, highlighting the antioxidant and anti-inflammatory function of LL in an IRE1α-XBP1-dependent manner.